A Review of The Use of Silk Fibroin in Sports Medicine/Injury - Fu, Yue (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Due to the increased promotion of sports and life span in many countries, sports medicine has become an important area for further research and investigation. With the advancement of technologies, tissue engineering is a prevalent topic for future development. Silk has been used for therapeutic strategies in many different areas since the Neolithic Age. Silk fibroin is a protein extracted from silk with a special structure with many potentials. This article will focus on the use of silk fibroin in common Musculoskeletal injuries which is divided into three areas: open wound injuries, fracture, and tissue engineering. However, traditional therapies for these three areas present limitations such as graft rejection and requiring a second surgery. Hence the article aims to explore the application of silk and how silk overcomes these limitations in medical applications when combined with other materials. SF demonstrates many potentials in medical applications based on the properties of excellent biocompatibility, causing a mild immune response, and supporting cell proliferation and tissue regeneration.